2006
DOI: 10.1111/j.1467-9450.2006.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

A Norwegian adaptation of the Penn State Worry Questionnaire: Factor structure, reliability, validity and norms

Abstract: A Norwegian version of the Penn State Worry Questionnaire (PSWQ) was administered to 304 undergraduate students together with the Beck Depression Inventory (BDI), the State-Trait Anxiety Inventory (STAI) and the Maudsley Obsessive Compulsive Inventory (MOCI). The PSWQ was also administered to a community sample comprising 879 subjects, together with the Beck Anxiety Inventory (BAI), the Beck Depression Inventory II (BDI II) and the White Bear Suppression Inventory (WBSI). Structural equation modeling showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
33
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 42 publications
(76 reference statements)
13
33
0
3
Order By: Relevance
“…(d) As expected, modest correlations between the K-PSWQ and the K-BAI and K-BDI provided strong evidence for convergent validity. These results are consistent with the previous study [Pallesen et al, 2006] which has demonstrated that the PSWQ correlated moderately with the BDI-II (r 5 .57) and the BAI (r 5 .53).…”
Section: Discussionsupporting
confidence: 95%
“…(d) As expected, modest correlations between the K-PSWQ and the K-BAI and K-BDI provided strong evidence for convergent validity. These results are consistent with the previous study [Pallesen et al, 2006] which has demonstrated that the PSWQ correlated moderately with the BDI-II (r 5 .57) and the BAI (r 5 .53).…”
Section: Discussionsupporting
confidence: 95%
“…No obstante, tal fi abilidad y/o validez no implica que los items evalúen un único factor (Nunnally y Bernstein, 1994). Podríamos concluir diciendo que tales propiedades son similares a las referidas para otras versiones del PSWQ, tales como las versiones inglesa (p.ej., Carter et al, 2005;Molina y Borkovec, 1994;Olatunji et al, 2007), francesa (Ladouceur et al, 1992), alemana (Stöber, 1995), holandesa (van Rijsoort et al, 1999, italiana (Meloni y Gana, 2001), noruega (Pallesen et al, 2006), turca (Yilmaz et al, 2008), coreana (Lim, Kim, Lee y Kwon, 2008) y china (Zhong, Wang, Li y Liu, 2009).…”
Section: Discussionunclassified
“…Una conclusión que podría derivarse de estos resultados congruentes con una estructura bifactorial del PSWQ es que el segundo factor, que representa «ausencia de preocupación», podría consistir en un artefacto metodológico más que en un factor relevante de preocupación. En línea con esta idea, algunos estudios recientes sugieren que se trata de un posible efecto (artefacto) metodológico (Olatunji et al, 2007;Yilmaz et al, 2008), sugerido también mediante análi-sis factorial confi rmatorio a través de modelos trifactoriales (un factor de preocupación y dos factores metodológicos -determinados estos por el sentido positivo o negativo de los items respectivamente) 2002, Meloni y Gana, 2001Pallesen et al, 2006).…”
unclassified
See 1 more Smart Citation
“…Items are rated on a 4-point scale ranging from 0 to 3 with summary scores ranging from 0 to 63. Scores from the BDI-II have demonstrated good psychometric properties (e.g., α = .93, Beck et al, 1996) and have been related to a cadre of psychological measures with theoretically consistent outcomes (e.g., r with STAI-T = .64, Karagozoglu, Mastgern, Baloglu, 2005; r with CES-D = .69, Kojima et al, 2002; r with BAI = .62, Pallesen, Nordhus, Carlstedt, Thayer, & Johnsen, 2006; r with MCSD-C = .05, Osman et al, 1997).…”
Section: Bdi-iimentioning
confidence: 98%